Lisfranc injuries. Issue 4 (April 2015) - Welck, M.J.; Zinchenko, R.; Rudge, B.
Abstract: Lisfranc injuries are commonly asked about in FRCS Orthopaedic trauma vivas. The term "Lisfranc injury" strictly refers to an injury where one or more of the metatarsals are displaced from the tarsus. The term is more commonly used to describe an injury to the midfoot centred on the 2nd tarsometatarsal joint. The injury is named after Jacques Lisfranc de St. Martin (1790–1847), a French surgeon and gynaecologist who first described the injury in 1815. 'Lisfranc injury' encompasses a broad spectrum of injuries, which can be purely ligamentous or involve the osseous and articular structures. They are often difficult to diagnose and treat, but if not detected and appropriately managed they can cause long-term disability. This review outlines the anatomy, epidemiology, classification, investigation and current evidence on management of this injury.